Phytoremediation : methods and reviews - Willey, Neil (Humana Press, 2007)
This book presents the most innovative recent methodological developments in phytoremediation research, and outlines a variety of the contexts in which phytoremediation has begun to be applied. A significant portion is devoted to groundbreaking methods for the production of plants that are able to degrade, take up, or tolerate the effects of pollutants. The book adopts a multidisciplinary approach to the examination of principles and practices of phytoremediation.